Resolving lineage assignation on Mycobacterium tuberculosis clinical isolates classified by spoligotyping with a new high-throughput 3R SNPs based method - Abadia, Edgar (2010)
Fil: Abadia, Edgar. Instituto de Genética y Microbiología, UMR8621, Equipo IGEPE, Universud, CNRS Université; Francia.